Description of SGPT Levels in Construction Workers Who Have an Active Smoking Habit - Eva Sapna; Nurul Inayati; Yudha Anggit Jiwantoro; Erna Kristinawati (Poltekkes Kemenkes Mataram, 2024)
Physical activity is body movement that requires skeletal muscles and can cause energy expenditure. Physical activity is divided into three, namely light, moderate and heavy physical activity. Construction workers who carry out heavy physical activity for 7 to 8 hours every day can lose a lot of energy and fluids as well as important micronutrients, one of which is iron. Apart from carrying out heavy physical activities, construction workers also have an active smoking habit, which means they are considered active smokers if they smoke more than 20 cigarettes every day. Smoking is something that can cause health problems and smoking has become the biggest cause of death in the world. Cigarette raw materials such as tar, nicotine and carbon monoxide are the main toxicants that can trigger the formation of free radicals. The Research objective is to determine the description of SGPT levels in construction workers who have an active smoking habit. The methods of this research design is descriptive observational research where this research was carried out using the enzymatic kinetic method a total of 28 samples based on calculations using the Slovin formula. The results of the research is examining SGPT levels in construction workers from 28 samples showed an increase in active smokers 11-15 years, namely 3 samples and active smokers 16-20 years, namely 2 samples, there was an increase or were outside the normal value, which is where the normal value of SGPT levels in men -men, namely 42 U/L. The conclusion of this research is showed that 5 of the 28 samples had increased SGPT levels with levels of 63 U/L, 58 U/L, 52 U/L and 49 U/L in 2 samples.